The Relationship of Hand Washing Behavior and Type of Latrine with Stunting Incident - Theodorus Teddy Bambang Soedjadi; Deli Syaputri; Samuel Marganda Halomoan Manalu; Leo Eykel Timanthar (Jurnal Penelitian Pendidikan IPA, 2024)
Stunting is a linear growth disorder in which a child's body is very short based on height-for-age with a Z-score threshold of < -2 SD. Silalahi sub-district has a stunting prevalence above 30%. Multi-dimensional factors, including environmental factors, cause stunted. Environmental factors that cause stunting are the mother's personal hygiene, sanitation, clean water, and drinking water sources. This study aimed to determine the relationship between washing hands with soap and latrine ownership with stunting in toddlers. Observational study with a case-control design in Silalahisabungan District, Dairi Regency. All stunted toddlers were taken as cases (78), and 78 toddlers were selected as controls, which were selected using systematic random sampling. The study results showed that there were stunting toddlers, namely 84 6% with the behavior of washing hands with soap did not meet the requirements, and 44.9% of toddlers suffering from stunting were in the age range of 21-40 months. Bivariate analysis using the chi-square test showed an effect of Handwashing with Soap (p=0.002, OR=2.727) and Latrine Ownership (p=0.001, OR=3.048) on the incidence of stunting in toddlers. Management of stunting events requires good coordination and collaboration between health workers, the government, and the community in reducing risk factors.